School management in Serbia: Key aspects of its relation to school success - Biljana Ratkovic Njegovan; Milos Crnomarkovic (Journal for East European Management Studies, 2012)
This paper provides an overview of the present state of management of school systems in the Republic of Serbia, and discusses the issue of introducing professional school management. Present underdevelopment of school management reflects the fact that decision making on virtually all aspects of education are strictly state centralized. Education process also suffers from poor cooperation between parents and school. The survey was conducted in 12 schools in the Republic of Serbia, the participants being head teachers, teachers, school psychologists and pedagogical consultants. In this paper, the key research findings are discussed with respect to the necessity of efficient school development planning and allowing education staff greater control over the education process. – – Dieser Artikel gibt einen Überblick über die derzeitige Situation der Verwaltung der Schulsysteme in der Republik Serbien. Die aktuelle Unterentwicklung des Schul-Managements reflektiert die Tatsache, dass die Entscheidungsfindung bezüglich fast aller Aspekte streng staatlich zentralisiert ist. Der Bildungsprozess leidet ebenfalls unter der schwachen Zusammenarbeit zwischen Schulen und Familien. Die Untersuchung wurde in 12 Schulen durchgeführt, die Befragten waren Schuldirektoren, Lehrer, Psychologen und Pädagogen. In diesem Artikel werden die Forschungsergebnisse diskutiert mit Bezug zur Notwendigkeit einer effizienten Schulentwicklungsplanung, die den Beschäftigten im Bildungswesen eine größere Kontrolle der Prozesse ermöglichen würde.
Keywords: 650; school management; planning; decentralization; Republic of Serbia